Hereditary Angioedema as a Metabolic Liver Disorder: Novel Therapeutic Options and Prospects for Cure - Ameratunga, Rohan; Bartlett, Adam; McCall, John; Steele, Richard; Woon, See-Tarn; Katelaris, Constance H. (Frontiers in Immunology, 2016)
Hereditary angioedema (HAE) is a rare autosomal dominant disorder caused by mutations of the SERPING1 or the Factor 12 genes. It is potentially fatal, particularly if not identified at an early stage. Apart from androgens, which are contraindicated in children and in pregnant women, a range of effective, albeit very expensive treatments have recently become available for HAE patients. The cost of these new treatments is beyond the reach of most developing countries. At this time, there is no cure for the disorder. In spite of mutations of the SERPING1 gene, autoimmunity and infections are not prominent features of the condition. Here we present the argument that HAE should be viewed primarily as a metabolic liver disorder. This conceptual paradigm shift will stimulate basic research and may facilitate new therapeutic approaches to HAE outlined in this paper. We suggest several novel potential treatment options for HAE from the perspectives of clinical immunology, molecular biology and liver transplantation. Many of these offer the prospect of curing the disorder. The effectiveness of these options are rapidly improving in many cases and their risks are decreasing. Given the very high costs of treating HAE, some of these curative options may become feasible in the next decade.